Pengaruh Brand Awareness dan Promosi Terhadap Minat Beli Konsumen Pada Toko Butik Perhiasan Emas Sararaholi Gunungsitoli - Mei Karuniawati Zai; Idarni Harefa; Yuterlin Zalukhu; Tiarni Duha (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to examine the influence of brand awareness and promotion on consumer purchase intention at Sararaholi Jaya Gold Jewelry Boutique, Gunungsitoli. The primary focus of the study is to understand how brand awareness and promotional activities carried out by the boutique impact consumer purchase intention. The research method used is quantitative, with data collected through questionnaires distributed to the boutique's consumers. The findings reveal that the promotion variable (X1) has a significant influence on consumer satisfaction by 89.2%, as indicated by an R Square value of 0.892. Meanwhile, the promotion variable (X2) also affects consumer purchase intention by 24.6%, as seen from an R Square value of 0.246. Overall, brand awareness (X1) and promotion (X2) together have a combined influence of 89.9% on customer satisfaction, as shown by an R Square value of 0.899, with the remaining 10.1% influenced by other variables not covered in this study. These findings highlight the importance of promotion strategies and brand awareness in increasing consumer purchase intention at Sararaholi Jaya Gold Jewelry Boutique.